1993
DOI: 10.1099/00222615-39-3-179
|View full text |Cite
|
Sign up to set email alerts
|

Identity of viridans streptococci isolated from cases of infective endocarditis

Abstract: Summary. The oral streptococci have undergone considerable taxonomic revision in recent years but there is still little information concerning associations between the newly defined species and disease. This study examined the identities of 47 strains of oral streptococci collected from 42 confirmed cases of infective endocarditis. By means of recently described physiological schemes, the most common species identified were Streptococcus sanguis sensu stricto (3 1.9 %), S. oralis (29.8 %) and S. gordonii (12.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
170
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(176 citation statements)
references
References 19 publications
2
170
0
4
Order By: Relevance
“…Many of the species of these five clusters are major constituents of the commensal microbiota of the human oral cavity and upper respiratory tract and are occasionally implicated in various pathologies. The anginosus group, formerly called "Streptococcus milleri" in some parts of the world (16), includes three recognized species (Streptococcus anginosus, Streptococcus intermedius, and Streptococcus constellatus) that are primarily associated with suppurative infections of tissues of the mouth and various body sites, including the meninges (9,37,44,54,56 Although they are commensals of the upper respiratory tract, S. pneumoniae is a major cause of both local and systemic infections and several of the other mitis group streptococci have long been recognized as important etiologic agents of subacute bacterial endocarditis (2,13); septicemia, particularly in neutropenic cancer patients (5,6,29); occasional cases of meningitis (8); and eye infections (1). The two species of the salivarius group associated with humans (Streptococcus salivarius and Streptococcus vestibularis) are usually considered to be of low virulence, although occasional life-threatening infections such as bacteremia and meningitis have been reported (11,43).…”
mentioning
confidence: 99%
“…Many of the species of these five clusters are major constituents of the commensal microbiota of the human oral cavity and upper respiratory tract and are occasionally implicated in various pathologies. The anginosus group, formerly called "Streptococcus milleri" in some parts of the world (16), includes three recognized species (Streptococcus anginosus, Streptococcus intermedius, and Streptococcus constellatus) that are primarily associated with suppurative infections of tissues of the mouth and various body sites, including the meninges (9,37,44,54,56 Although they are commensals of the upper respiratory tract, S. pneumoniae is a major cause of both local and systemic infections and several of the other mitis group streptococci have long been recognized as important etiologic agents of subacute bacterial endocarditis (2,13); septicemia, particularly in neutropenic cancer patients (5,6,29); occasional cases of meningitis (8); and eye infections (1). The two species of the salivarius group associated with humans (Streptococcus salivarius and Streptococcus vestibularis) are usually considered to be of low virulence, although occasional life-threatening infections such as bacteremia and meningitis have been reported (11,43).…”
mentioning
confidence: 99%
“…There are several reports which have shown that the viridans streptococci are the most common cause of infective endocarditis (5,6) and the viridans group streptococcal bacteremia is more frequently inducible in patients with severe periodontal disease (7,8). However, there are no reports on the collective analysis of the oral VGS and its relation with infective endocarditis in cases of periodontitis.…”
Section: Contextmentioning
confidence: 94%
“…It frequently causes bacteremia and infective endocarditis (IE) [1]. Kozarov et al examined 129 samples of DNA extracted from 29 atheromatous individuals for the presence of bacterial 16S rDNA sequences.…”
Section: Introductionmentioning
confidence: 99%